Tooth reattachment: An immediate esthetic restorative procedure for crown root fracture - Meenu G Singla; Rakesh Mittal; Anchal Singla (Wolters Kluwer Medknow Publications, 2012)
Crown root fractures in the maxillary anterior region represent an intriguing challenge for clinicians. An interdisciplinary approach based on exposing fractured margins and the definitive prosthetic rehabilitation represent the standard modality of treatment for these conditions to restore the appropriate biologic dimension and esthetics. However, if the margins of the fragment and the tooth show perfect juxtaposition with no interfragmentary space and immediate esthetic replacement is needed, reattachment of the fractured segment using adhesives may be indicated. The aim of this case report is to describe the treatment of a crown root fracture at CEJ of an endodontically treated tooth having porcelain fused to metal crown by means of metal post placement and reattactment of the fragment using Glass ionomer cement with follow up of one year. Conclusion: Reattachment of a tooth fragment is a viable technique that restores function and aesthetics with a very conservative approach in a single visit and can be considered when treating patients with crown/root fractures of the anterior teeth.